Penetapan Tradisi Boka Dalam Perkawinan Suku Buton Ditinjau Dari Perspektif Hukum Islam - Dewi, Citra; Angga, La Ode; Fataruba, Sabri (BAMETI Customary Law Review, 2024)
The Boka tradition in Butonese marriages reflects a social and cultural reality that remains deeply rooted in society, despite shifting values ​​due to modernization. In the Butonese context, Boka is a gift from the groom to the bride before marriage, which is legally equivalent to the concept of dowry as regulated in Law Number 1 of 1974 in conjunction with Law Number 16 of 2019 concerning Marriage. This study aims to determine and explain the procedure for determining Boka in the customary law system and the Islamic legal perspective on Boka in Butonese marriages. This study uses a normative legal research method with a statutory and conceptual approach. The legal materials used include primary, secondary, and tertiary sources, obtained through literature studies and relevant symposiums. The results show that the Boka determination procedure begins with the pabita stage (initial proposal), continues with family deliberation, and ends with the handover of Boka before the marriage ceremony. The value of Boka varies based on social stratification (kaomu, walaka, papara), but still upholds the principle of deliberation. From an Islamic legal perspective, the Boka tradition is acceptable as long as it is implemented with the principles of justice, simplicity, and willingness, in line with the purpose of the dowry in Islam as a form of appreciation, not a burden.